Pemanfaatan Tumbuhan Melati Air (Echinodorus Palaefolius) dengan Sistem Constructed Wetlands untuk Pengolahan Grey Water - Monik Kasman; Peppy Herawati; Niken Aryani (Jurnal Daur Lingkungan, 2018)
Grey water, according to its quantity and characteristics, is potential to be source of raw water. To address this, a common approriate method has been implemented in Indonesia, is constructed wetlands system. This is due to vegetation diversity, simple construction, flexible, easy and low cost in operation and maintenance, as well as high estetics. This research is focused on observing the effects of detention time and system of constructed wetlands reactors using Echinodorus palaefolius vegetation to reduce biological oxygen demand (BOD) and Total suspended solid (TSS). The detention time varied by 3 days, 4 days, 5 days, 6 days and 7 days. The system of constructed wetlands reactors varied by blank reactor , as a control without vegetation (CW 1); reactor with few flowers (CW 2); reactor with vegetation having leaves less than (<)20 (CW 3) and reactor with vegetation having leaves more than (>)20 (CW 4). The results showed that the detention time and the system of constructed wetlands reactors influences in reducing BOD and TSS. Concentration of BOD and TSS efluen decreases as the detention time increase. Besides, these concentrations decrease, as the amount of leaves increase. The concentration of BOD and TSS ranges (1,6 – 3,22) mg/L) and (0,003 – 0,147) mg/L.Keywords :    Constructed wetlands; Echinodorus palaefolius; Grey water; BOD, TSS